Project Based Learning (PjBL) Model on the Mathematical Representation Ability - Ratnasari, Nining; Tadjudin, Nilawati; Syazali, Muhamad; Mujib, Mujib; Andriani, Siska (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the comparison of students 'mathematical representation ability through the Project Based Learning (PjBL) Model and the students' mathematical representation ability through the conventional model. The PjBL model is a student-centered, innovative, project-based learning model and positioned teachers as effective facilitators in the contextual learning related to real life situation. This research employed quasi-experimental design. The research applied the posttest only non-equivalent control group design through randomized cluster sampling. The data collection technique used was test. The instrument used to collect the data was the essay test. Data analysis was conducted using independent sample t-test. The result of the data calculation through the Independent-Sample T-Test test obtained the significance level of 0.913 means that the students’ mathematical representation ability was better after the learning through Project Based Learning (PjBL) model was conducted compared to the students' mathematical representation ability through a conventional model. This means that the PjBL model is more influential on students' mathematical representation ability.